Mechanical Vegetative Management - Rien M. Visser; Bruce Hull; Sarah F. Ashton; Martha C. Monroe (EDIS, 2009)
Revised! FOR180, an 8-page illustrated fact sheet by Rien M. Visser, Bruce Hull, Sarah F. Ashton, and Martha C. Monroe, discusses the mechanical means to manage vegetation in interface forests and reviews available technologies that may be most useful in small, visible, and sensitive forests that are typical of the interface. Includes references. Published by the UF School of Forest Resources and Conservation, October 2008.